Avaliação da dor em bezerras amochadas com ferro quente após distintos protocolos de analgesia - Favaretto, Bruna Peruzzo (2021)
The behavior of the calves after dehorn with hot iron indicates whether the pain mitigation protocol was efficient. The aim of this study was to evaluate the effects of different non-steroidal anti-inflammatory drugs in mitigating pain in calves dehorned, by assessing behavior, cortisol levels, heart rate, lying time and lying bouts. For that, 33 calves were used, divided into three groups: Control group (GI), no NSAID; Control group (GI), did not receive any anti-inflammatory drugs; Group II received a dose of flunixin meglumine and Group III received a dose of meloxicam. All animals were previously sedated with xylazine and received local anesthesia in the corneal nerve. Behavioral variables were assessed at 2, 4, 6, 8 and 10 hours after the procedure. Heart rate was measured between the cuckolding of one horn and the other for one minute in duration with the use of a stethoscope. The lying time and lying bouts was measured for 24 hours pre-dehorn and 24 hours after dehorn using a device (HOBO) and cortisol was measured at -15 and at 15, 120 and 180 min after the dehorn. There was no difference between groups in the animals behavior, heart rate, cortisol levels, lying time and lying bouts. There is no influence on the pain control of calves that receive anti-inflammatory drugs and are previously sedated and anesthetized locally before hot iron dehorning.